The relationship of communication satisfaction to job satisfaction of secondary school teachers in Singapore - Sim, Kean Kok. (2009)
This study is aimed at finding out if there is a positive relationship between teachers' satisfaction with the school communication and their satisfaction with their work. It is also to find out teachers' responses to the various aspects of communication in schools and their perception of the importance of these aspects.